2017
DOI: 10.20944/preprints201706.0088.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Control Strategy for Grid Connected Inverters Under Unbalanced Network Conditions - A DOb Based Decoupled Current Approach

Abstract: Penetration of grid connected inverters (GCI) has arisen in power systems due to increasing integration of renewable sources. However, restrictive grid codes require that renewable sources connected to the grid with power electronic systems must be properly connected and appropriate currents must be injected to support stability of the grid under grid faults. Simultaneous injection of symmetrical positive and negative sequence currents is mandatory to support stabilization of grid at the instant of grid faults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 20 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…The weight parameter in equation ( 2) is reversely adjusted according to the error [11]. The weight is constantly adjusted through repeated training until the training error reaches the expected value.…”
Section: Combination Of Traditional Pi Regulation Strategy and Bp Neural Algorithmmentioning
confidence: 99%
“…The weight parameter in equation ( 2) is reversely adjusted according to the error [11]. The weight is constantly adjusted through repeated training until the training error reaches the expected value.…”
Section: Combination Of Traditional Pi Regulation Strategy and Bp Neural Algorithmmentioning
confidence: 99%
“…The PCI controller achieves more accurate and faster current regulation [23] than the traditional PI and PR controllers [45]. Improved traditional PI controller (29) is written in the following equation:…”
Section: Pci Controllermentioning
confidence: 99%
“…In [28], the fractional‐order PI controller has been improved to reduce harmonic component tracking error and to enhance the response of the system. In [29], disturbance observer‐based proportional decoupled current controller is presented for controlling negative sequences. In α β / normalSTRF, for steady‐state errors and current tracking errors, the PR controller [3, 9, 30], direct power control algorithm [31], hysteresis control strategy [32], and the MPC [22, 33] or other advanced control techniques have been discussed for the current regulation.…”
Section: Introductionmentioning
confidence: 99%
“…The role of power converters is very unique since the converters are the interfaces enabling the synchronization, voltage control, current control and power flow control in the MG and SG [5,7,8]. A number of studies can be found in the literature regarding the control of three-phase VSI, specifically in view of controlling the imbalance of power in the MG [9][10][11][12][13]. All of these established works offer complexity, since they are designed to maintain pure sinusoidal voltages as the output of the VSI, whose conception dates back to the 1980s due to the stringent supply requirements of the three-phase motors [14][15][16][17].…”
mentioning
confidence: 99%